Essays on the Integration of New Energy Sources into Existing Energy Systems - Luise Röpke (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2015)
This volume was prepared by Luise Röpke while she was working at the Ifo Institute. It was completed in December 2013 and accepted as a doctoral thesis by the Department of Economics at the University of Munich. It includes three self-contained chapters about aspects of the integration of new energy sources into existing energy systems. Three aspects regarding the introduction of new energy sources into existing fossil fuel markets are analyzed. Chapters one and two deal with this topic in two theoretical dynamic models of resource extraction. The energy market model of chapter one consists of heterogeneous energy sources and a capacity constrained green backstop resource. In chapter two, an energy market with increasing substitutability between exhaustible and renewable energy sources is analyzed. In both models, different effects are worked out that a policymaker has to take into account when designing an energy-political instrument. It is shown that different climate policies affect the speed of resource extraction differently. The third chapter contains a more applied analysis of the German electricity market. It focuses on how the development of renewable energies will affect security of electricity supply. In a cost-benefit analysis, the value of supply security is compared with its costs of provision.
Keywords: D61; Q30; Q42; Q48; 330; Erneuerbare Energie; Energiewirtschaft; Energiesubstitution; Nachhaltige Energieversorgung; Energieversorgung; Förderung erneuerbarer Energien; Wohlfahrtsanalyse; Theorie; Erneuerbare Energie; Energiewirtschaft; Energiesubstitution; Nachhaltige Energieversorgung; Energieversorgung; Förderung erneuerbarer Energien; Wohlfahrtsanalyse; Theorie